Viruses utilize ubiquitination systems to escape TLR/RLR-mediated innate immunity - Huang, Shanzhi; Cheng, Anchun; Wang, Mingshu; Yin, Zhongqiong; Huang, Juan; Jia, Renyong (Frontiers in Immunology, 2022)
When the viruses invade the body, they will be recognized by the host pattern recognition receptors (PRRs) such as Toll like receptor (TLR) or retinoic acid-induced gene-I like receptor (RLR), thus causing the activation of downstream antiviral signals to resist the virus invasion. The cross action between ubiquitination and proteins in these signal cascades enhances the antiviral signal. On the contrary, more and more viruses have also been found to use the ubiquitination system to inhibit TLR/RLR mediated innate immunity. Therefore, this review summarizes how the ubiquitination system plays a regulatory role in TLR/RLR mediated innate immunity, and how viruses use the ubiquitination system to complete immune escape.